Peran Stakeholder dalam Mewujudkan Pemenuhan Hak Anak Melalui Program Kartu Identitas Anak - Nur Risma Lutfiana Al Marza; Wulandari, Septi; Junadi (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
In 2019 in Bojonegoro District, child identity cards began to be issued. However, currently, some people still consider KIA to be unimportant, thus hampering the fulfillment of children's civil rights, where stakeholders have a role in conveying information about the importance of KIA. This research aims to determine all the stakeholders who contribute to implementing the child identity card program by children's rights. The case study methodology combined with qualitative research with the main research subjects are stakeholders in the Child Identity Card program in Bojonegoro District. Based on observations, especially in Bojonegoro, the role of stakeholders between the community and the government cannot be said to be good. One of the difficulties faced is the lack of community involvement in implementing KIA. Therefore, for the KIA program to be implemented as an equitable manifestation of children's rights, community and government stakeholders must work together.